Health Conditions and Memory Performance: a study with older adult women - Alice Milani Nespollo; Samira Reschetti Marcon; Nathalie Vilma Pollo de Lima; Tatiane Lebre Dias; Mariano Martínez Espinosa
ABSTRACT Objective: to verify the correlation between health condition and memory performance of older adult women in the community. Method: Analytical cross-sectional study developed with 28 older adult women living in Cuiabá-MT. They answered the Mini-Mental State Examination (MMSE), and a shortened Geriatric Depression Scale (GDS-15) to screen for dementia and depression symptoms. Memory skills were assessed through Rey Auditory Verbal Learning Test (RAVLT). Results: The mean age was 66.36 years and 75% of the participants had educational level higher than 7 years. The MMSE mean score was 28.45. The correlations found were: educational level and immediate memory (r = 0.49; p = 0.008); delayed recall and immediate memory (r = 0.71; p < 0.001); memory recognition and immediate memory (r = 0.43; p = 0.021) and recognition memory with delayed recall (r = 0.47; p = 0.012). Conclusion: High scores in the MMSE and a satisfactory health perception among the participants were evident. There was no correlation between memory performance and health perception.